CHEMICAL AND PHYSICAL PROPERTIES OF SEPANG (Caesalpinia sappan l.) INSTANT DRINK: REVIEW OF PROPORTION OF WHITE EGGS, MALTODEXTRIN, FEASIBILITY OF THEIR BUSINESS - Agustina Intan Niken Tari, Nugraheni Retnaningsih & (Proceeding of International Congress, 2014)
Sepang drink made of sepang wood, lemon grass leaf, cloves, ginger and sugar. This Beverages included inthe category of soft drinks which can be used to cure coughs, dysentery and stomach pain. The purpose ofresearch is to assess the effect of egg white and maltodextrin on the chemical and physical properties ofinstant drink (Caesalpinia sappan L.), and determine the feasibility of making a sepang of instantbeverages. This study used a completely randomized design factorial 2 x 3 with three replications.Parameter observations carried out on the chemical nature of instant sepang include: moisture and ashcontent and a sepang of instant physical properties include: pH, solubility and viscosity; and financialfeasibility. The results showed that the water content and low ash content achieved in the interaction ofegg white treatment 7.5% and maltodextrin 15%, respectively 2.947% and 1.036%. Treatmentconcentrations of egg white does not give a real effect on the pH and viscosity instant sepang, butsignificant effect on the solubility of instant sepang with the highest solubility of 85.45% on 2.5% eggwhite treatment. Maltodextrin significant effect on pH, solubility, viscosity instant cup with a pH of 7.79,solubility 86.90%, and viscosity 1.046 cP at 15% maltodextrin treatments. Analysis of a sepang instantbeverage business has a value of 296.43 Kg BEP or USD 8,172,509.89; PP 2.92 or 2 years 9 months; ROI33.30%; NPV USD 60,809,276.62; and PI 1.2 thus the business of making a sepang instant beverages isfeasible.Keywords: chemicalâphysical properties, feasibility, sepang instant drink